A wire for high-strength ship plate steel with super-large energy to work (EGW) and a preparation method thereof
Patent Information
- Application Number
- CN202410583448.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-11
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-05-11
AI Technical Summary
[0006]本发明提供了一种高强船板钢超大线能量EGW用丝材及其制备方法,通过向药芯粉末中添加LaB6纳米颗粒,使其在电弧高温下分解并与丝材中的Ti、Al、N、S、Mn等元素发生反应,生成La-Al-Ti-Mn-O复合氧化物、BS和BN,促进针状铁素体析出,有效抑制奥氏体长大,解决了现有技术中由于晶粒细化程度差和不能有效促进针状铁素体形成所导致的焊缝强度与低温韧性差的问题
[0020]1.本发明通过引入LaB6纳米颗粒在EGW过程中与O、Al、Ti、Mn反应,生成的La-Al-Ti-Mn-O复合氧化物均匀分布在基体中,在周围形成了贫Mn区促进了针状铁素体的析出,在焊缝凝固时诱发针状铁素体异质形核;LaB6纳米颗粒在EGW过程中与焊缝中的S、N反应,生成的BS和BN分布在晶界处,在焊缝凝固时阻碍奥氏体长大,细化晶粒,同时使从奥氏体析出的针状铁素体更加细小,从而抑制上贝氏体和侧板条铁素体等有害组织的析出,使焊缝金属在EGW超大线能量热输入下(大于600kJ/cm)仍保持较高的低温韧性。
Smart Images

Figure CN118342161B_ABST
Abstract
Description
Technical fields:
[0001] This invention belongs to the field of welding materials technology, and in particular relates to a high-strength ship plate steel ultra-high heat input EGW (gas electric vertical welding) wire and its preparation method. Background technology:
[0002] As larger ships become the mainstream trend in the shipbuilding industry, the steel used in ships is also developing towards higher strength and greater thickness. The continuous improvement of shipbuilding standards has rendered traditional welding processes inefficient enough to meet the requirements of rapid large-scale shipbuilding. High heat input welding (HEAW) technology, due to its high welding efficiency, has been widely used in the welding of thick plates. Among them, electro-gas welding (EGW) technology has a concentrated heat source and can use high current and voltage (typically welding current greater than 300A and arc voltage greater than 30V) to complete the welding, generally 3 to 4 times that of ordinary submerged arc welding. Its efficiency is typically 30 times that of ordinary arc welding, and the wire feeding speed can reach 45 times that of ordinary wire feeders, resulting in high welding efficiency. Therefore, EGW is used as the primary welding method in the welding of large hull assemblies. However, high-efficiency high heat input welding technology requires a large amount of heat input. For example, the actual welding energy of EGW can exceed 600 kJ / cm. Under such a high heat input, the microstructure of the weld joint will be severely deteriorated, resulting in undesirable structures such as upper bainite and side strip ferrite, which increases the probability of crack propagation and greatly reduces the toughness of the weld joint.
[0003] Currently, countries like Japan and South Korea often improve the low-temperature toughness of welds by introducing dispersed high-melting-point metal oxides into the weld metal. These oxides utilize the pinning effect to inhibit austenite grain growth and act as nucleation sites within the austenite grains, inducing the formation of acicular ferrite. Patent application CN200910046732.3 discloses a "high-toughness submerged arc welding wire," characterized by high yield strength and tensile strength of the weld metal, excellent low-temperature toughness, and resistance to high heat input. Its chemical composition is as follows: C: 0.08–0.15%, Si: ≤0.1%, Mn: 1.90–2.20%, S: ≤0.010%, P: ≤0.020%, Ni: 0.10–0.30%, Cu: <0.35%, with the remainder being Fe. By rationally proportioning Mn, C, Si, and Ni, the low-temperature toughness of the weld at a welding heat input of 35 kJ / cm is effectively improved, while also exhibiting appropriate yield strength and tensile strength. Patent application CN102310299A discloses "a flux-cored welding wire suitable for high heat input welding". By simultaneously controlling the ratio of Ti and B elements, it suppresses the formation of proeutectoid ferrite during cooling and promotes the precipitation of acicular ferrite, effectively improving the impact toughness of the deposited metal. However, the problem of austenite coarsening is not improved.
[0004] Wu Jiani's article "Study on the Influence of Rare Earth Y on the Microstructure and Properties of Ship Plate Steel and its High Heat Input Welding" points out that when steel containing rare earth Y is heated to the austenitizing temperature, a large number of uniformly dispersed inclusions will be generated. During the phase transformation cooling process, these inclusions can increase the area fraction of acicular ferrite and remove impurities. They exist in the form of rare earth sulfur oxides, sulfides, and oxides at grain boundaries and within grains, but the original austenite grains are still relatively coarse.
[0005] In summary, the use of appropriate element ratios and the introduction of dispersed high-melting-point precipitates to promote the nucleation of acicular ferrite or inhibit the growth of austenite has been studied to some extent, and can improve the strength or low-temperature toughness of welds. However, the relatively low heat input during welding limits the improvement of weld performance. Therefore, it is necessary to explore a novel strengthening method to improve the strength and low-temperature toughness of welds under ultra-high heat input welding conditions. Summary of the Invention:
[0006] This invention provides a high-strength ship plate steel wire for ultra-high heat input (EGW) welding and its preparation method. By adding LaB6 nanoparticles to the flux core powder, it decomposes under high-temperature electric arc and reacts with elements such as Ti, Al, N, S, and Mn in the wire to generate La-Al-Ti-Mn-O composite oxides, BS, and BN. This promotes the precipitation of acicular ferrite and effectively inhibits austenite growth, solving the problems of poor weld strength and low-temperature toughness caused by poor grain refinement and inability to effectively promote the formation of acicular ferrite in the prior art.
[0007] This invention is achieved through the following technical solution:
[0008] A high-strength ship plate steel wire for ultra-high heat output (EGW) consists of an outer sheath and a powder coating. The powder coating is 15%-30% filled. The outer sheath is made of H08A low-alloy steel strip, and the inner powder coating comprises the following components by weight percentage: Mn 5.0%-7.5%, Si 1.0%-3.0%, Ni 1.0%-3.5%, Mo 0.5%-1.5%, Ti ≤0.5%, LaB6 0.25%-1.0%, rutile 2.5%-3.5%, fluorite ≤1.25%, feldspar 2.5%-4.0%, mullite 1.0%-2.5%, with the remainder being Fe. Among these, rutile, fluorite, feldspar, and mullite constitute a slagging agent.
[0009] Preferably, the powder comprises the following components by weight percentage: Mn 5.5%-7.5%, Si 1.5%-3.0%, Ni 1.0%-3.0%, Mo 1.0%-1.5%, Ti ≤0.5%, LaB6 0.25%-0.5%, rutile 2.5%-3.5%, fluorite ≤1.25%, feldspar 2.5%-4.0%, mullite 1.0%-2.5%, with the remainder being Fe.
[0010] Mullite, fluorite, feldspar, and rutile in the flux core powder act as slag-forming agents, stabilizing the electric arc, adjusting the melt viscosity, and protecting the weld droplets and molten pool. LaB6 decomposes at the high temperature of the electric arc and reacts with elements such as Ti, Al, N, S, and Mn in the wire to generate La-Al-Ti-Mn-O composite oxides, BS, and BN. During the austenite transformation, a Mn-depleted region forms around the uniformly distributed La-Al-Ti-Mn-O composite oxides. As an austenite stabilizing element, Mn depletion promotes the precipitation of acicular ferrite, while fine BS and BN, mainly distributed at grain boundaries, effectively inhibit austenite growth. Due to grain refinement and the precipitation of abundant acicular ferrite, the strength and low-temperature toughness of the weld are greatly improved.
[0011] Preferably, the LaB6 particle size is 50-150 nm, and the average size is 100 nm.
[0012] This invention also protects a method for preparing the above-mentioned high-strength ship plate steel ultra-high heat output (EGW) wire, comprising the following steps:
[0013] S1. Place Mn, Si, Ni, Mo, Ti and LaB6 in a ball mill jar in proportion and ball mill to obtain mixed powder; place the mixed powder and rutile, fluorite, feldspar and mullite powders into a drying oven at 100℃ for 1 hour, and then put them into a Y-type powder mixer to mix for 30-40 minutes to obtain core powder.
[0014] S2. Place the H08A steel strip into a drying oven at 100°C and keep it at that temperature for 1 hour. After cooling, roll the steel strip into a U-shape using forming rolls. Then fill the U-shaped steel strip with the core powder obtained in step S1 and roll it into core filaments using a drawing die.
[0015] Preferably, in step S1, the process parameters of the ball mill are set as follows: 30 minutes of forward rotation, 10 minutes of stop, 30 minutes of reverse rotation, and a total time of 70 minutes.
[0016] Preferably, in step S2, the diameter of the core wire is 1.6 mm.
[0017] LaB6 is a nanoscale particle that is prone to agglomeration. It needs to be uniformly mixed with the metal powder in the core using ball milling. This invention achieves optimal ball milling parameters for mixing the core powder and LaB6 nanoparticles by continuously adjusting the milling process parameters. The core powder and LaB6 nanoparticles used in the core have an average size of 100 nm. A high ball-to-powder ratio (6:1) can lead to some agglomeration of LaB6 particles. This is because the ball-to-powder ratio determines the flow space of the core powder and the number of times it is mixed by ball impact. When the ball-to-powder ratio is too high, the flow space of the core powder is small, thus reducing the number of times it is mixed by ball impact. Furthermore, the high viscosity of LaB6 particles results in some core powder not being uniformly mixed. To solve this problem, this invention improves the ball milling parameters and reduces the ball-to-powder ratio, ultimately resulting in a uniform distribution of LaB6 nanoparticles on the surface of the core powder.
[0018] This invention also protects the application of the aforementioned wire material in high-strength ship plate steel ultra-high heat input welding (EGW). The ultra-high heat input welding employs a double-wire vertical EGW, with the base material bevel designed as a single-sided V-shaped bevel, a bevel angle of 20°, a gap of 6–8 mm, and a blunt edge of 0–1 mm. The extension length of the two welding wires is 40 mm, the welding torch angle is 6°–10°, the distance from the rear wire to the backing is 23 mm, and the spacing between the two welding wires is 17 mm. The welding process parameters are: the rear wire uses DC positive polarity, fixed without oscillation, current 526.7–554.2 A, voltage 47.6–50.9 V; the front wire uses DC reverse polarity, oscillation width 15–20 mm, current 531.6–564.7 A, voltage 49.5–51.3 V; the shielding gas is CO2, and the velocity is 30–60 mm·min. -1 The heat input is 602.4–627.3 kJ·cm⁻¹. -1 .
[0019] The beneficial effects of this invention are as follows:
[0020] 1. This invention introduces LaB6 nanoparticles that react with O, Al, Ti, and Mn during the EGW process. The resulting La-Al-Ti-Mn-O composite oxide is uniformly distributed in the matrix, forming a Mn-depleted region around it, which promotes the precipitation of acicular ferrite. During weld solidification, this induces heterogeneous nucleation of acicular ferrite. During the EGW process, the LaB6 nanoparticles react with S and N in the weld, generating BS and BN distributed at the grain boundaries. During weld solidification, these hinder austenite growth, refine the grains, and make the acicular ferrite precipitated from austenite even smaller. This suppresses the precipitation of harmful structures such as upper bainite and side lath ferrite, allowing the weld metal to maintain high low-temperature toughness even under EGW ultra-high heat input (greater than 600 kJ / cm).
[0021] 2. This invention solves the problem of LaB6 particle agglomeration by changing the ball-to-powder ratio in the ball milling process, so that LaB6 nanoparticles are uniformly distributed on the core powder; the prepared wire has good weld formation after welding high-strength ship plate steel, with no surface defects and internal pores.
[0022] In summary, this invention significantly improves the low-temperature toughness of high-strength ship plate steel after welding by adding LaB6 nanoparticles to the flux core powder to react with O, Ti, Al, and N in the weld during welding, and by using an improved ball milling process to promote the uniform distribution of the generated reinforcing particles in the matrix and grain boundaries of the weld structure. This solves the problem of coarse grains and low toughness caused by excessive heat input in ultra-high heat input EGW. Attached image description:
[0023] Figure 1 This is a microstructure of the weld metal after welding the flux-cored wire prepared in Example 2.
[0024] Figure 2 This is a microstructure of the weld metal after welding the flux-cored wire prepared in Comparative Example 1. Detailed implementation method:
[0025] Those skilled in the art will understand that the techniques disclosed in the following embodiments represent those discovered by the inventors that work well in the practice of this invention. However, many changes can be made to the specific embodiments disclosed, still obtaining the same or similar results without departing from the spirit and scope of the invention.
[0026] Example 1:
[0027] A high-strength ship plate steel wire for ultra-high heat input welding (EGW) consists of an outer sheath and a flux powder. The flux powder filling rate is 20%. The outer sheath is made of H08A low-alloy steel strip, and the inner core is filled with flux powder. The diameter of the flux-cored wire is 1.6 mm. Based on a total mass percentage of 100%, the flux powder comprises the following components: Mn 6.0%, Si 1.5%, Ni 2.0%, Mo 1.5%, Ti 0.5%, LaB6 0.25%, rutile 3%, fluorite 1.0%, feldspar 3.5%, mullite 2.0%, with the remainder being Fe. Rutile, fluorite, feldspar, and mullite constitute a slagging agent.
[0028] The specific steps for preparing the above-mentioned high-strength ship plate steel wire for ultra-high heat output (EGW) are as follows:
[0029] Step S1: Mn, Si, Ni, Mo, Ti and LaB6 are placed in a ball mill jar in a certain proportion and ball milled to obtain a mixed powder. The ball milling process parameters are set as follows: forward rotation for 30 min, stop for 10 min, reverse rotation for 30 min, total time for 70 min, ball-to-powder ratio of 5:1. Then, the mixed powder and slag-forming agent (rutile, fluorite, feldspar and mullite) powder are placed in a drying furnace and heated to 100℃ and kept at that temperature for 1 h. Then, they are added to a Y-type powder mixer and mixed for 30 min to obtain a uniformly mixed core powder.
[0030] Step S2: The H08A steel strip is placed in a large drying oven and heated to 100°C and kept at that temperature for 1 hour. After cooling, the H08A steel strip is rolled into a U-shape using forming rollers in a dust-free workshop. Then, the uniformly mixed powder obtained in step S1 is added to the U-shaped drug coating according to the above filling rate through a powder feeding device. Finally, the drug core wire with a diameter of 1.6 mm is rolled into a drawing die.
[0031] Comparative Example 1:
[0032] Referring to Example 1, the difference is that the core powder does not contain LaB6 nanoparticles. The other steps are the same as in Example 1.
[0033] Comparative Example 2:
[0034] Referring to Comparative Example 1, the difference is that the ball-to-powder ratio in the ball milling process is 6:1. Other steps are the same as in Example 1.
[0035] Example 2:
[0036] A high-strength ship plate steel wire for ultra-high heat output (EGW) consists of two parts: an outer sheath and a powder. The powder filling rate is 15%. The outer sheath is made of H08A low-alloy steel strip, and the inner powder is filled with the following components by weight percentage: Mn 6.0%, Si 1.5%, Ni 2.0%, Mo 1.5%, Ti 0.5%, LaB6 0.5%, rutile 3%, fluorite 1.0%, feldspar 3.5%, mullite 2.0%, and the remainder is Fe. Among them, rutile, fluorite, feldspar, and mullite constitute a slagging agent.
[0037] The specific steps for preparing the above-mentioned high-strength ship plate steel wire for ultra-high heat output (EGW) are as follows:
[0038] Step S1: Mn, Si, Ni, Mo, Ti and LaB6 are placed in a ball mill jar in a certain proportion and ball milled to obtain a mixed powder. The ball milling process parameters are set as follows: forward rotation for 30 min, stop for 10 min, reverse rotation for 30 min, total time for 70 min, ball-to-powder ratio of 5:1. Then, the mixed powder and slag-forming agent (rutile, fluorite, feldspar and mullite) powder are placed in a drying furnace and heated to 100℃ and kept at that temperature for 1 h. Then, they are added to a Y-type powder mixer and mixed for 30 min to obtain a uniformly mixed core powder.
[0039] Step S2: The H08A steel strip is placed in a large drying oven and heated to 100°C and kept at that temperature for 1 hour. After cooling, the H08A steel strip is rolled into a U-shape using forming rollers in a dust-free workshop. Then, the uniformly mixed powder obtained in step S1 is added to the U-shaped drug coating according to the above filling rate through a powder feeding device. Finally, the drug core wire with a diameter of 1.6 mm is rolled into a drawing die.
[0040] Example 3
[0041] A high-strength ship plate steel wire for ultra-high heat output (EGW) consists of two parts: an outer sheath and a powder. The powder filling rate is 15%. The outer sheath is made of H08A low-alloy steel strip, and the inner powder is filled with the following components by weight percentage: Mn 6.0%, Si 1.5%, Ni 2.0%, Mo 1.5%, Ti 0.5%, LaB6 0.75%, rutile 3%, fluorite 1.0%, feldspar 3.5%, mullite 2.0%, and the remainder is Fe. Among them, rutile, fluorite, feldspar, and mullite constitute a slagging agent.
[0042] The specific steps for preparing the above-mentioned high-strength ship plate steel wire for ultra-high heat output (EGW) are as follows:
[0043] Step S1: Mn, Si, Ni, Mo, Ti and LaB6 are placed in a ball mill jar in a certain proportion and ball milled to obtain a mixed powder. The ball milling process parameters are set as follows: forward rotation for 30 min, stop for 10 min, reverse rotation for 30 min, total time for 70 min, ball-to-powder ratio of 5:1. Then, the mixed powder and slag-forming agent (rutile, fluorite, feldspar and mullite) powder are placed in a drying furnace and heated to 100℃ and kept at that temperature for 1 h. Then, they are added to a Y-type powder mixer and mixed for 30 min to obtain a uniformly mixed core powder.
[0044] Step S2: The H08A steel strip is placed in a large drying oven and heated to 100°C and kept at that temperature for 1 hour. After cooling, the H08A steel strip is rolled into a U-shape using forming rollers in a dust-free workshop. Then, the uniformly mixed powder obtained in step S1 is added to the U-shaped drug coating according to the above filling rate through a powder feeding device. Finally, the drug core wire with a diameter of 1.6 mm is rolled into a drawing die.
[0045] Example 4:
[0046] A high-strength ship plate steel wire for ultra-high heat output (EGW) consists of two parts: an outer sheath and a powder. The powder filling rate is 15%. The outer sheath is made of H08A low-alloy steel strip, and the inner powder is filled with the following components by weight percentage: Mn 6.0%, Si 1.5%, Ni 2.0%, Mo 1.5%, Ti 0.5%, LaB6 1.0%, rutile 3%, fluorite 1.0%, feldspar 3.5%, mullite 2.0%, and the remainder is Fe. Among them, rutile, fluorite, feldspar, and mullite constitute a slagging agent.
[0047] The specific steps for preparing the above-mentioned high-strength ship plate steel wire for ultra-high heat output (EGW) are as follows:
[0048] Step S1: Mn, Si, Ni, Mo, Ti and LaB6 are placed in a ball mill jar in a certain proportion and ball milled to obtain a mixed powder. The ball milling process parameters are set as follows: forward rotation for 30 min, stop for 10 min, reverse rotation for 30 min, total time for 70 min, ball-to-powder ratio of 5:1. Then, the mixed powder and slag-forming agent (rutile, fluorite, feldspar and mullite) powder are placed in a drying furnace and heated to 100℃ and kept at that temperature for 1 h. Then, they are added to a Y-type powder mixer and mixed for 30 min to obtain a uniformly mixed core powder.
[0049] Step S2: The H08A steel strip is placed in a large drying oven and heated to 100°C and kept at that temperature for 1 hour. After cooling, the H08A steel strip is rolled into a U-shape using forming rollers in a dust-free workshop. Then, the uniformly mixed powder obtained in step S1 is added to the U-shaped drug coating according to the above filling rate through a powder feeding device. Finally, the drug core wire with a diameter of 1.6 mm is rolled into a drawing die.
[0050] High-strength ship plate steel was welded using flux-cored welding wires prepared in Examples 1-4 and Comparative Examples 1-2, respectively. The base material used was EH36 steel with the composition shown in Table 2, and the plate thickness was 60 mm. After being processed into 150 mm × 500 mm test plates, a V-groove was cut with a groove angle of 17°. The welding parameters are shown in Table 1.
[0051] Table 1 Experimental welding parameters
[0052]
[0053] Table 2 Chemical composition of the parent material (wt.%)
[0054]
[0055] The microstructure of the weld metal after welding the flux-cored wire prepared in Example 2 is shown in the figure. Figure 2 The microstructure is predominantly composed of bainite and Widmanstätten. The microstructure of the weld metal after welding of the flux-cored wire prepared in Comparative Example 1 is shown below. Figure 1 The microstructure is mainly composed of acicular ferrite.
[0056] The performance of the welds after welding high-strength ship plate steel with flux-cored wires prepared in Examples 1-4 and Comparative Examples 1-2 was further tested. Tensile tests were conducted using a WDW-300 microcomputer-controlled electronic universal testing machine to determine the yield strength, tensile strength, and elongation of each specimen. The test methods were in accordance with GB / T2652 "Tensive Testing of Welds and Cladding Metals". In addition, the weld metal was cut from high-heat-input weld metal samples and processed into standard Charpy-V impact specimens according to GBT17493-2008. The impact tests were conducted on an Instron Dynatup 9200 series drop hammer impact testing machine. The test temperature was set at -40℃, and the cooling medium was ethanol. Flux-cored wires without LaB6 nanoparticles and flux-cored wires with a ball milling ratio of 6:1 were used as comparative examples. The performance test results are shown in Table 3 below.
[0057] Table 3. Test results of the mechanical properties of weld metals in Examples 1-4 and Comparative Examples 1-2
[0058]
[0059] As can be seen from the comparison of Examples 1-4 and Comparative Examples 1-2 in Table 2, the addition of LaB6 nanoparticles to the flux powder effectively improves the mechanical properties of the weld. Optimizing the ball-to-powder ratio during the flux powder preparation process can also improve the mechanical properties of the subsequent weld.
Claims
1. A high-strength ship plate steel wire for ultra-high thermal energy (EGW) applications, characterized in that, It consists of two parts: an outer sheath and a powder. The powder filling rate is 15%-30%. The outer sheath is an H08A alloy steel strip, and the inner powder is filled with powder. The powder, based on a total mass percentage of 100%, includes the following components: Mn 5.0%-7.5%, Si 1.0%-3.0%, Ni 1.0%-3.5%, Mo 0.5%-1.5%, Ti≤0.5%, LaB6 0.25%-1.0%, rutile 2.5%-3.5%, fluorite≤1.25%, feldspar 2.5%-4.0%, mullite 1.0%-2.5%, and the remainder is Fe. Among them, rutile, fluorite, feldspar, and mullite constitute a slagging agent. LaB6 is a nano-sized particle and needs to be mixed evenly with the metal powder in the core using ball milling. The ball-to-powder ratio is 5:
1. The particle size of LaB6 is 50-150 nm, and the average size is 100 nm.
2. The filament according to claim 1, characterized in that, The powder comprises the following components by weight percentage: Mn 5.5%-7.5%, Si 1.5%-3.0%, Ni 1.0%-3.0%, Mo 1.0%-1.5%, Ti≤0.5%, LaB6 0.25%-0.5%, rutile 2.5%-3.5%, fluorite≤1.25%, feldspar 2.5%-4.0%, mullite 1.0%-2.5%, with the remainder being Fe.
3. The method for preparing the high-strength ship plate steel ultra-high heat output (EGW) wire according to claim 1, characterized in that, Includes the following steps: S1. Mn, Si, Ni, Mo, Ti and LaB6 are placed in a ball mill jar in a certain proportion and ball milled to obtain a mixed powder. The ball-to-powder ratio is 5:
1. The mixed powder and rutile, fluorite, feldspar and mullite powders are placed in a drying oven and kept at 100℃ for 1 h. Then they are placed in a Y-type powder mixer and mixed for 30-40 min to obtain core powder. S2. Place the H08A steel strip into a drying oven at 100°C and keep it at that temperature for 1 hour. After cooling, roll the steel strip into a U-shape using forming rolls. Then fill the U-shaped steel strip with the core powder obtained in step S1 and roll it into core filaments using a drawing die.
4. The preparation method according to claim 3, characterized in that, In step S1, the process parameters for the ball mill are set as follows: forward rotation for 30 min, stop for 10 min, reverse rotation for 30 min, and the total time is 70 min.
5. The preparation method according to claim 3, characterized in that, In step S2, the diameter of the core wire is 1.6 mm.
6. The application of the high-strength ship plate steel wire for ultra-high heat output (EGW) as described in claim 1, characterized in that, For dual-wire vertical EGW, the base material bevel is designed as a single-sided V-shaped bevel with a bevel angle of 20°, a gap of 6-8mm, and a blunt edge of 0-1mm. The extension length of the two welding wires is 40mm, the welding torch angle is 6°-10°, the distance from the rear wire to the backing wire is 23mm, and the spacing between the two welding wires is 17mm. The welding process parameters are: the rear wire is DC positive polarity, fixed without oscillation, current 526.7-554.2A, voltage 47.6-50.9V; the front wire is DC negative polarity, oscillation width is 15-20mm, current 531.6-564.7A, voltage 49.5-51.3V; the shielding gas is CO2, and the velocity is 30-60mm·min. -1 The heat input is 602.4~627.3 kJ·cm. -1 .
Citation Information
Patent Citations
High-toughness submerged arc welding wire
CN101817122A
Hidden arc welding flux-cored wire suitable for high heat input welding
CN102310299A
Flux-cored wire for master cable energy forced shaping, and preparation and application method thereof
CN102554519A
Special fine-diameter flux-cored wire for hot-working die repairing surfacing
CN105081611A